The Effect of Comic Book’s Story Character and Color on Farmers’ Knowledge Gain About Small Sheep Farm Management in Kulur, District of Majalengka, West Java, Indonesia - Suparjo R Satmoko; A Jahi (Faculty of Animal Science, Bogor Agricultural University, 2009)
What kind of comic book’s character was best suited to small sheep farmers, what was their preferred color, and what were the combined effects of such characters and color on the farmers’ knowledge about small sheep farm management? These questions directed researchers to design a 2x2 factorial quasi experimental study. Four farmer groups were involved in the study. The results indicated that the comic book characters’ effect on the farmers’ knowledge gains was highly significant; the comic book’s color effect on the farmers’ knowledge gains was also significant, and the combined effect of the comic book’s character and colors was not significant. Further tests demonstrated that the farmer group exposed to the colored comic book with human character performed much better than the other three groups in the posttests. So, the conclusion was that farmers preferred the colored comic book with human character to learn the small sheep farm management. Key words: comic book, story character, color, sheep management, farmer’s knowledge